2013
DOI: 10.1902/jop.2012.120366
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Dyslipidemia and Diabetes Mellitus on Chronic Periodontal Disease

Abstract: It could be concluded that dyslipidemia did not influence periodontal conditions in participants with normal health or those with DM2. However, age, smoking habits, and especially DM2 were significantly associated with loss of CAL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 44 publications
0
20
0
Order By: Relevance
“…Studies have reported incidence and progression of periodontal disease in patients with DMt2 in Brazil; 18–20 however, none of them evaluated the effects of chronic periodontal disease progression on DM outcomes. It is deemed important to evaluate patients from a specific geographic area with low socioeconomic and educational status who receive medical treatment from the public health care system, in which the majority of patients with DM and those presenting periodontal disease seek treatment 21 .…”
mentioning
confidence: 99%
“…Studies have reported incidence and progression of periodontal disease in patients with DMt2 in Brazil; 18–20 however, none of them evaluated the effects of chronic periodontal disease progression on DM outcomes. It is deemed important to evaluate patients from a specific geographic area with low socioeconomic and educational status who receive medical treatment from the public health care system, in which the majority of patients with DM and those presenting periodontal disease seek treatment 21 .…”
mentioning
confidence: 99%
“…[9] showed that TC was significantly increased in patients with Type II DM; however, periodontal disease did not show any significant correlation. The results of this study are contrary to the findings of our study regarding periodontal diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that Type II DM is positively correlated with hyperlipidemia and periodontitis does not show a definite association;[9] however, other studies have shown a positive association between periodontitis and hyperlipidemia. [1011]…”
Section: Introductionmentioning
confidence: 99%
“…STZ has highly selective toxic effects on islet cells in experimental animals, which leads to direct destruction of pancreatic β cells of the islet tissue or causes an immune response and decreases the insulin secretion of islets, which leads to diabetes (14,15). This model has advantages, including a simple preparation method, low dosage, low toxicity and specific islet cell damage, and it has become the preferred method of establishing a rat model of diabetes (16).…”
Section: Discussionmentioning
confidence: 99%